2012
DOI: 10.1002/pc.22279
|View full text |Cite
|
Sign up to set email alerts
|

The tensile behavior of off‐axis loaded plant fiber composites: An insight on the nonlinear stress–strain response

Abstract: Composites in load‐bearing applications are often exposed to off‐axis loads. For plant fiber composites (PFCs) to be seriously and readily considered in structural applications, knowledge and reliable prediction of their response to off‐axis loads is critical. This article (i) characterizes the stress–strain response, (ii) investigates the tensile properties, and (iii) analyses the fracture modes, of unidirectional flax‐polyester composites subjected to off‐axis tensile loading. A key finding of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 52 publications
4
81
0
1
Order By: Relevance
“…5b), plant fibre composites exhibit a substantial (up to 50 %) reduction in stiffness initially (in the strain range of 0-0.4 %) before stabilising ( Fig. 5b; Bensadoun et al 2016;Kersani et al 2015;Shah 2016;Shah et al 2012a). Such variations in stiffness with applied strain make it difficult to compare measured (from single plant fibre tests) and predicted (using ROM for composites) fibre stiffness.…”
Section: Measurement Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…5b), plant fibre composites exhibit a substantial (up to 50 %) reduction in stiffness initially (in the strain range of 0-0.4 %) before stabilising ( Fig. 5b; Bensadoun et al 2016;Kersani et al 2015;Shah 2016;Shah et al 2012a). Such variations in stiffness with applied strain make it difficult to compare measured (from single plant fibre tests) and predicted (using ROM for composites) fibre stiffness.…”
Section: Measurement Conditionsmentioning
confidence: 99%
“…At least six 250 mm long and 15 mm wide specimens were tested at a crosshead speed of 2 mm/min. The stress-strain curve of each specimen was used to measure its tensile modulus E c [in the strain range of 0.025-0.10 %, following (Baets et al 2014;Shah et al 2012a)], tensile strength r c and failure strain e c .…”
Section: Materials and Preparationmentioning
confidence: 99%
“…transverse tearing (figure 8b) to (iii) ductile-brittle fracture resulting from uniquely oriented layers failing in distinctly different manners (figure 8c). The orientation of the nanofibrils in the different layers of the tubes would have had a considerable effect on the tensile properties and fracture mechanism [28]. Typically, fibre-dominated ductile failure through fibre fracture or fibre pull-out is characteristic of fibres oriented in the loading direction (i.e.…”
Section: Longitudinal Tensile Propertiesmentioning
confidence: 99%
“…In particular, the bottom ring sections had higher stiffness and strength, but lower failure strain in comparison with ring sections from the top ( figure 7). It is notable that such a transition in stress-strain profiles and properties is observed in polymer composites when fibre orientation is changed [12,28]. Steeper slopes indicate fibres aligned closer to the loading direction, whereas gentle slopes indicate fibres aligned at an angle to the loading direction [12,28].…”
Section: Transverse Tensile Propertiesmentioning
confidence: 99%
“…Baley et al [19] reported that the transverse modulus of flax fibres was 8 GPa, compared to a longitudinal modulus of 59 GPa. However, Shah et al reported that flax fibres in a twisted yarn had a transverse modulus of 3.9 GPa, a longitudinal modulus of 46 GPa and a shear modulus of 2 GPa [20]. The results emphasize the need for composite researchers to fully appreciate and acknowledge the mechanical anisotropy of natural fibres caused by their highly complex structure.…”
Section: Introductionmentioning
confidence: 95%